ANALYSIS OF THE PHYSICAL CONDITION OF ARCHERY ATHLETES UKM UBBG - Zulheri Is (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to analyze the physical condition of UBBG UKM archery athletes based on five components of physical fitness, namely upper body muscle strength, core muscle endurance, flexibility, balance, and coordination. The study involved 20 athletes who underwent a series of physical tests, namely a push-up test for upper body muscle strength, a plank test for core muscle endurance, a sit-and-reach test for flexibility, a one-leg balance test for balance, and a throw-and-catch for coordination. The results showed that the majority of athletes were in good physical condition, although there were some areas that still needed more attention. In the push-up test, 50% of athletes were in the Good category, 25% in the Very Good category, and 25% in the Moderate category. In the core muscle endurance test, 45% of athletes were in the Good category, 30% in the Very Good category, and 25% in the Moderate category. In the flexibility test, 40% of athletes were in the Good category, 20% in the Very Good category, and 40% in the Medium category. In the balance test, 50% of athletes were in the Good category, 35% in the Very Good category, and 15% in the Medium category. Finally, in the coordination test, 75% of the athletes were in the Good and Very Good categories. Overall, the study shows that most athletes are in good physical condition, with some areas that need to be improved to support optimal archery performance.